SAT0492 Whipple's Disease Mimicking Rheumatoid Arthritis Leads To Misdiagnosis, Treatment Failure, and Prolonged Disease Course: A Single-Center Case Series of Seven Patients. (15th July 2016) - Glaser, C.; Rieg, S.; Scholz, C.; Wiech, T.; Voll, R.E.; Thiel, J.; Venhoff, N.
Abstract : Background: Whipple's disease (WD) is a rare disease caused by a chronic infection with Tropheryma whipplei (TW). Joint involvement is common. The rarity, the broad spectrum of symptoms, and the similarity to rheumatoid arthritis (RA) may result in misdiagnosis. Without antibiotic treatment WD may be fatal, misleadingly induced immunosuppressive treatment may even accelerate disease progression. Objectives: To describe the clinical presentation, the disease course with respect to immunosuppressive treatment and the response to antibiotic treatment in patients with WD presenting with inflammatory arthritis. Methods: Retrospective single center observational study of seven patients. Medical charts were screened for articular and extra-articular symptoms. Diagnosis of WD was made by histological analysis using periodic acid-Schiff stain (PAS) and/or polymerase chain reaction (PCR). Results: Median age at disease onset was 57 years (range 34- 64), six patients were male. The median time until diagnosis of WD was 5 years. All patients presented with polyarthritis with a predominantly symmetric pattern in five and a chronic, intermittent disease course in six patients. Affected joints were: wrists (5/7), MCP (5/7), knees (5/7), PIP (3/7), hips (2/7), elbow (2/7), shoulder (2/7). All patients had increased C-reactive protein and/or ESR and were negative for RF and anti-CCP-antibodies. Three had erosive arthritis. Thus, initially all patients were classified as a seronegative RA following EULAR/ACR criteria with a median DAS28 of 4.34 (range 2.8–6.28). All but one patient received antirheumatic treatment consisting of prednisone (n=6), combined with methotrexate (n=5) or leflunomide (n=4). Three patients were treated with at least one biologic agent (anti-TNFα, abatacept, rituximab, tocilizumab). All patients showed insufficient treatment response, in one disease course was even worsened by the use of biologicals. Finally diagnosis of WD was made by a combination of positive PAS staining and a positive TW-PCR test in three patients. In five patients PCR was positive in at least two different sites. In all patients TW was detected in synovial fluid. Extra-articular manifestations of WD were frequent, but mainly mild and unspecific for WD, GI-symptoms were mild or absent even in patients with TW detected in small bowel biopsy. Five patients received long-term trimethoprin/sulfamethoxazole, two started with doxycycline plus hydroxychloroquine. Five patients had to change antibiotic regimen due to side effects or microbial resistance. All had a good treatment response with improvement of arthritis and extra-articular manifestations. Two are still on antibiotics while five patients could already stop treatment. Conclusions: WD is rare and can mimic RA. Patients are therefore at risk of not only a delay of diagnosis but also of receiving insufficient or even worsening treatment. Hence, seronegative RA with a prolonged disease course and insufficient treatment response should be reevaluated for WD. Disclosure of Interest: None declared